Enhancement The Growth of Snakehead (Channa striata) With Addition of Dragon Fruit Peel Flour to the Diet - Rakhmawati Rakhmawati; Tulas Aprilia; Agung Kurniawan (Program Pascasarjana Universitas Sriwijaya, 2021)
Snakehead (Channa striata) is a fish that grows relatively slowly, but is a typical Sumatran fish with high albumin content and economic value. This makes this fish a very prospect to be developed. Meanwhile, dragon fruit peel is one of the wastes that can be used for diet raw materials and contains vitamins and minerals that have the potential to be useful for increasing growth in fish. This study aims to determine the growth performance of snakehead fed by adding dragon fruit peel flour. This study used test animals, namely snakehead fish juvenile with size of 1.06 ± 0.02 g/fish. Experiment of fish reared in aquarium measuring of 35 x 45 x 90 cm, filled with water as high as 15 cm without aeration. The experiment diets consisted of 5 types, namely feed added with 0% dragon fruit flour (control); 0.5; 1.0; 1.5 and 2.0% of feed. Each treatment was repeated three times. Snakehead was reared for 60 days and fed three times a day on an ad satiation basis. The parameters observed in this study were the survival rate and growth performance of snakehead fish. The results showed that the survival rate between treatments was not significantly different, namely in the range of 97.76 - 100%. Meanwhile, the specific growth rate and feed efficiency of snakehead which added 2% to the diets were the highest, namely 8.66 ± 0.04% and 67.83 ± 2.31%. The conclusion of this study was the addition of dragon fruit peel flour at 2% enhanced the growth performance of snakehead.